Corynoxine B ameliorates HMGB1-dependent autophagy dysfunction during manganese exposure in SH-SY5Y human neuroblastoma cells. (February 2019) - Yan, Dongying; Ma, Zhuo; Liu, Chang; Wang, Can; Deng, Yu; Liu, Wei; Xu, Bin
Abstract: Manganese (Mn) has recently come into the limelight as an important environmental risk factor for neurodegenerative disorders. Although multiple neurotoxicity of Mn have been extensively studied, the exact mechanism of Mn-induced autophagic dysregulation is still poorly understood. The main aim of this study was to explore the role of cytosolic high-mobility group box 1 (HMGB1)-dependent autophagy in Mn-induced autophagic dysregulation and neurotoxicity. SH-SY5Y cells were treated with culture solution (control) and three different concentrations of Mn (50, 100, and 200 μM) for 24 h to detect the effect of Mn on HMGB1-dependent autophagy. We found Mn could increase the HMGB1 mRNA level and its cytosolic translocation and dysregulate autophagy, and Mn-induced alpha-synuclein overexpression interfered with the interaction of HMGB1 and Beclin1, to subsequently promote Beclin1 binding to Bcl2. Another important finding was the neuroprotective role of corynoxine B (Cory B) in Mn-induced autophagic dysregulation and neurotoxicity. We set up six experimental groups: control (culture solution); 200 μM Mn treatment; 100 μM Cory B-alone treatment; and three different pretreated concentrations of Cory B (25, 50, and 100 μM). Our results showed that Cory B ameliorated Mn-induced autophagic dysregulation and neurotoxicity partly by dissociating HMGB1 from alpha-synuclein and inhibiting mTOR signaling. Highlights: Mn-induced autophagy is related to HMGB1-Beclin1 binding. Mn-induced α-SYN protein disturbs HMGB1-dependent autophagy. Cory B dissociates HMGB1 from α-SYN to bind to Beclin1. Cory B ameliorates Mn-induced autophagic dysregulation and neurotoxicity.